(untitled) (Journal of Pathology of Nepal, 2019)
Histoplasmosis is a fungal infection caused by a dimorphic, saprophytic fungus Histoplasma capsulatum with primary predilection for the lungs and disseminated infections occurring rarely. Our case illustrates the case of disseminated adrenal histoplasmosis in an immunocompromised 42-year-old diabetic man. Radiological diagnosis suggested bilateral malignant adrenal mass, most likely metastasis. FNAC yielded blood only. Excisional biopsy from left adrenal gland, Hematoxylin & Eosin staining along with special stains as Periodic Acid Schiff and Grocott’s Methenamine Silver were performed to yield the concluding diagnosis of histoplasmosis.